2011
DOI: 10.3109/08820139.2011.604864
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of TLR9 by a Suppressive Oligodeoxynucleotides Can Ameliorate the Clinical Signs of EAN

Abstract: Susceptible-strain animals immunized with P2 peptide could generate the disease of experimental autoimmune neuritis (EAN) with inflammation and demyelination of peripheral nerve. A myriad of transcription factors and inflammatory cytokines have been found to participate in this process; however, the roles of toll-like receptors (TLRs) are poorly understood in EAN. The aim of this study is to explore the role of TLR9 in the pathogenesis of EAN. The EAN was induced in Lewis rat by immunization with P2(53-78) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previous studies revealed that iODNs inhibit the immune response by blocking the stimulatory effects of CpG motifs [4,15]. In animal models, iODNs can be used to prevent or treat diseases characterized by persistent immune activation, including collagen-induced arthritis [16], inflammatory arthritis [5], silicosis [9], autoimmune neuritis [17], papillomas [18], ocular inflammation [19], and toxic shock [20]. In this study, we examined the immune effect of iODNs in mouse immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that iODNs inhibit the immune response by blocking the stimulatory effects of CpG motifs [4,15]. In animal models, iODNs can be used to prevent or treat diseases characterized by persistent immune activation, including collagen-induced arthritis [16], inflammatory arthritis [5], silicosis [9], autoimmune neuritis [17], papillomas [18], ocular inflammation [19], and toxic shock [20]. In this study, we examined the immune effect of iODNs in mouse immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is induced by injecting P2 peptide in complete Freund’s adjuvant into the hind footpads of Lewis rats. When animals with EIN were treated with H154, markers of inflammation and disease severity were significantly reduced [89].…”
Section: Tlr Specific Sup Odnmentioning
confidence: 99%
“…The levels of TLRs like TLR2, TLR4, TLR6, and TLR9 transcripts were significantly upregulated in the sciatic nerves of rats with EAN; the pattern of expression of certain TLRs varied during the course of EAN and their expression also correlated with disease severity 16‐18 . However, clinical studies on TLRs are limited only to altered expressions of TLR2 , TLR4 , TLR6 , and TLR9 genes in peripheral blood cells, and they also demonstrated a correlation between TLR expression and the severity of GBS 16,19 . These preclinical and clinical studies suggest an important role of TLRs in determining the severity of EAN and GBS.…”
Section: Introductionmentioning
confidence: 83%
“…[16][17][18] However, clinical studies on TLRs are limited only to altered expressions of TLR2, TLR4, TLR6, and TLR9 genes in peripheral blood cells, and they also demonstrated a correlation between TLR expression and the severity of GBS. 16,19 These preclinical and clinical studies suggest an important role of TLRs in determining the severity of EAN and GBS.…”
Section: Introductionmentioning
confidence: 99%